Adsorption assisted double stage cooling and desalination employing silica gel + water and AQSOA-Z02 + water systems - Ali, Syed Muztuza (2017)
We have presented adsorption assisted cooling and desalination employing zeolites and silica gel as adsorbents and water as adsorbate for useful cooling effects at the evaporator and the desalination effects at the condenser. Since the conventional adsorption cooling system works at low evaporator pressure, only a small portion of the adsorption capacity is used for water production. To overcome these limitations, we have modelled and simulated a cooling cum desalination system, where the adsorption cooling system (stage-1) is amalgamated with the adsorption desalination system (stage-2). Therefore, the overall performance is improved by heat recovery between the condenser and the evaporators of both cycles. The simulation results are presented in terms of specific cooling power (SCP), specific daily water production (SDWP), coefficient of performance (COP), performance ratio (PR) and overall conversion ratio (OCR). These results are also compared with experimental data. It is found that the adsorption beds of cooling cycle should be housed with AQSOA-Z02 zeolites for more cooling capacity, whereas the sorption elements of desalination cycle are fabricated with silica gels for more SDWP. The proposed system produces 26% more water and 45% more cooling capacity as compared with conventional equivalent adsorption cooling and desalination systems.